Particle detectors in curved spacetime quantum field theory - Hodgkinson, Lee (2013)
Unruh-DeWitt particle detector models are studied in a variety of time-dependent and time-independent settings. We work within the framework of first-order perturbation theory and couple the detector to a massless scalar field. The necessity of switching on (off) the detector smoothly is emphasised throughout, and the transition rate is found by taking the sharp-switching limit of the regulator-free and finite response function.